Immune-Mediated Mechanisms in Cofactor-Dependent Food Allergy and Anaphylaxis: Effect of Cofactors in Basophils and Mast Cells - Muñoz-Cano, Rosa; San Bartolome, Clara; Casas-Saucedo, Rocío; Araujo, Giovanna; Gelis, Sonia; Ruano-Zaragoza, Maria; Roca-Ferrer, Jordi; Palomares, Francis; Martin, Margarita; Bartra, Joan; Pascal, Mariona (Frontiers in Immunology, 2021)
Cofactors may explain why in some cases food ingestion leads to anaphylaxis, while in others it elicits a milder reaction or tolerance. With cofactors, reactions become more severe and/or have a lower allergen threshold. Cofactors are present in up to 58% of food anaphylaxis (FAn). Exercise, NSAIDs or alcohol are those most frequently described, although the underlying mechanisms are poorly known. Several hypotheses have suggested the influence of these cofactors on basophils and mast cells (MC). Exercise has been suggested to enhance MC activation by increasing plasma osmolarity, redistributing blood flow, and activating adenosine and eicosanoid metabolism. The NSAIDs cofactor effect has been related to cyclooxygenase inhibition and, therefore, prostaglandin E2 (PGE2) production. Indeed, overexpression of the adenosine receptor 3 (A3R) gene has been described in NSAID-dependent FAn; A3R activation potentiates FcεRI-induced MC degranulation. Finally, alcohol has been associated with an increase of histamine levels by inhibition of diamino oxidase (DAO), and also with an increase of extracellular adenosine by inhibition of its uptake. However, most of these mechanisms have limited evidence and further studies are urgently required. In conclusion, the study of the immune-related mechanisms involved in food allergy reactions enhanced by cofactors is of the utmost interest. This knowledge will help in the design of both tailored treatments and prophylactic strategies that, nowadays, are non-existent.